A new genus and species of anchialine Hymenosomatidae (Crustacea, Decapoda, Brachyura) from Samar, Philippines - Husana, Daniel Edison M.; Tan, Swee Hee; Kase, Tomoki (Zootaxa, 2011)
A new genus and species of brachyuran crab, Samarplax principe (family Hymenosomatidae) is described from an anchialine cave in Samar Island, Philippines. This cavernicolous species lacks rostrum and has degenerated eyes, possesses two small spines at the lateral margin of the carapace, has a proportionally shorter projected merus of the third maxilliped, an almost flat epistome and brush-like setae instead of teeth along the cutting edges of the chelae. The complete loss of visual organs and pigmentation, the long but slender ambulatory legs and large egg size suggest a completely hypogeal lifestyle for this species. This is the first species of Hymenosomatidae recorded from an anchialine cave in the Philippines exhibiting true troglomorphic adaptations.